2019
DOI: 10.1039/c9tc01608b
|View full text |Cite
|
Sign up to set email alerts
|

Highly-efficient and all-solution-processed red-emitting InP/ZnS-based quantum-dot light-emitting diodes enabled by compositional engineering of electron transport layers

Abstract: All-solution-processed red-emitting InP/ZnS-based QD-LEDs with a record ηEQE of 4.24% are successfully fabricated through the compositional engineering of colloidal ZnO NPs, which act as the electron transport layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Therefore, the gap states and electron conductivity of ZnO or doped ZnO were more important concerns, compared to the CBM alignments with InP QDs. The above arguments are also consistent with the conclusions in Chen, Tang, and co-worker’s work published recently . This work studied the effects of differently modified ZnO in InP QLEDs and concluded that the combination of chloride-passivation of surface trap states and Mg doping of ZnO NPs can prevent exciton quenching at the QDs/ETL interface.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the gap states and electron conductivity of ZnO or doped ZnO were more important concerns, compared to the CBM alignments with InP QDs. The above arguments are also consistent with the conclusions in Chen, Tang, and co-worker’s work published recently . This work studied the effects of differently modified ZnO in InP QLEDs and concluded that the combination of chloride-passivation of surface trap states and Mg doping of ZnO NPs can prevent exciton quenching at the QDs/ETL interface.…”
supporting
confidence: 90%
“…The above arguments are also consistent with the conclusions in Chen, Tang, and coworker's work published recently. 109 This work studied the effects of differently modified ZnO in InP QLEDs and concluded that the combination of chloride-passivation of surface trap states and Mg doping of ZnO NPs can prevent exciton quenching at the QDs/ETL interface. Since the first report of InP-based QLED in 2011, the performance of InP-based QLED was greatly enhanced through the efforts on the synthesis of high-quality InP QDs and optimization of the QLED device structure.…”
mentioning
confidence: 99%
“…This phenomenon is caused by the neighboring ZnMgO NPs and the presence of surface defects in the emitting layer and the ETL. Modifying the ETL is an effective way to balance the mobility of charge injection. , , InP-based QDs with a (DMA) 3 P phosphorus source for QLEDs have not been extensively studied, and only few papers focused on this subject because of the difficulty in obtaining high-performance QLEDs. ,, Therefore, further research is essential to increase the device performance of these QLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the unprecedented leap in the device performance, further enhancements are still limited by imbalanced charge injection into the QD emissive layer (EML). Because the state-of-the-art device architecture has a multilayered structure in which the QD EML is sandwiched between an organic hole-transporting layer (HTL) and an inorganic electron-transporting layer (ETL), the intrinsic differences in carrier mobility in these organic/inorganic materials cause undesirable asymmetry of charge densities at the EML. , Moreover, to enhance the device lifetime, it is also critical to prevent excessive electron leakages because excess electrons can also damage organic HTLs or the interfaces. Numerous efforts have been made to enhance hole injection: multiple HTLs having cascade energy levels or dipole interlayers have been implemented between the HTL and EML for energy level alignment; HTLs containing p-dopant or mixed multiple hole-transporting materials (HTMs) have been applied to increase conductivity; QDs blended with conducting polymers have been used as EMLs. Xuan et al fabricated hybrid white LEDs using a composite of poly­( N -vinylcarbazole) (PVK) and CdSe/CdS core/shell QDs as an EML and achieved a maximum luminance of 180 cd/m 2 and a current efficiency of 0.21 cd/A, and their red/blue devices also demonstrated enhanced performance. , Wang and co-workers introduced PVK as a dopant in a blue ZnCdSe-based QD EML and achieved an EQE of 8.8% with a maximum luminance of 13 800 cd/m 2 . Liang et al used a PVK-mixed CdSe/CdS/ZnS QD EML in an inverted structure and achieved an EQE of 16.8% with a current efficiency of 19 cd/A.…”
mentioning
confidence: 99%